Study of the influence concentration difference of copper in properties of cerium nanopowder - Hateef, Areej Adnan; Dhahri, Essebti; Rasheed, Mohammed; Kadhim, Habiba; Abbas, Zahraa; Hassan, Noor (Physics and Chemistry of Solid State, 2024)
Various concentrations (3%, 6%, 9%) of copper added to pure cerium oxide nanopowder were prepared by the sol-gel method. The prepared samples were examined using different techniques to understand their surface compositional and morphological properties. The face-centered cubic (FCC) structure of CeO2:Cu was identified from X-ray diffraction (XRD) analysis. It was observed that the calculated crystalline size of the prepared powders decreased when the copper concentration increased from 3% to 9%. The surface morphology and shape of CeO2:Cu were examined by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) which images confirmed CeO2:Cu nanopowders prepared has cubic shape and uniformly well-dispersed . Moreover, a slight distortion in the surface morphology was obtained when the Cu concentration was increased. Meanwhile Bond formation between cerium and oxygen (Ce-O) was confirmed using FTIR spectroscopy. While UV and visible spectroscopy determined band gap energies of 2.63 eV for pure cerium oxide while this value decreasing when concentration of copper increasing; this because absorptance increasing powder measuered . This paper can provide possible mechanisms after results showed CeO2:Cu nanopowders have a good activity antibacterial against many pathogenic bacteria. Hence, CeO2:Cu can be used as a biomaterial in nanobiotechnology applications.